Strongest Correlation Between Contrast Sensitivity and Morphological Characteristics in Bilateral nAMD - Hoffmann, Laura; Rossouw, Petra; Guichard, Maria-Magdalena; Hatz, Katja (Frontiers in Medicine, 2021)
In patients with neovascular age-related macular degeneration (nAMD) there is often an inconsistency between their subjective visual impairment and a still relatively preserved standard Early Treatment of Diabetic Retinopathy Study (ETDRS) best corrected visual acuity. Therefore, in order to better capture the specific functional defects in nAMD, other tests need to be evaluated. In a previous study, we reported contrast sensitivity of the better eye to best correlate with near distance and distance vision related quality of life in patients with bilateral nAMD. Here, we evaluated Pelli-Robson contrast sensitivity, ETDRS visual acuity, low luminance visual acuity and Radner maximum reading speed and correlated them with several morphologic parameters as measured on fundus autofluorescence imaging, optical coherence tomography and optical tomography angiography in 54 patients. A multiple regression analysis was performed which correlated each visual function parameter with the anatomic features. The results showed the strongest correlations between the total area of macular geographic atrophy as well as the percentage of geographic atrophy in the central 1mm and contrast sensitivity. Further, the regression model selected the total area of macular geographic atrophy, the photoreceptor inner and outer segments interface disruption score, the presence of subretinal fibrosis in the central 1mm and the central retinal thickness as the variables that explained 71% of the variation in contrast sensitivity when including all eyes. Hence, our results suggest that among the evaluated measures of vision, contrast sensitivity is best correlated with the morphologic impairment in bilateral nAMD. Thus, contrast sensitivity may complement ETDRS visual acuity in clinical trials and serve as a standard diagnostic tool in clinical practice.